2020
DOI: 10.3889/oamjms.2020.5350
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Butyl Para-Aminobenzoate and Iodoform as a Secondary Prevention of Dry Socket: A Systematic Review

Abstract: BACKGROUND: Dry socket is the most common post-operative complication following a dental extraction and one of the most studied complications in dentistry. Many researchers have attempted to find a successful method for its primary prevention. However, this area remains controversial as no single method has gained universal acceptance. Therefore, secondary prevention of this case is still needed to prevent the continuing effects of dry sockets and other complications resulting from inadequate dry socket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Neocone, on the other hand, gave total pain reduction and accelerated recovery. Moreover, Kusumastiwi PO et al 15 undertaken a research to evaluate the treatment results of dressings containing a mixture of butyl aminobenzoate, eugenol, and iodoform, as well as other dry socket remedies, in terms of pain solace and socket curing, and they found that all of the treatments that include in the evaluation have the same goal of relieving the patient 's suffering. The findings are challenging to evaluate due to the variety of treatments and measuring scales used.…”
Section: Resultsmentioning
confidence: 99%
“…Neocone, on the other hand, gave total pain reduction and accelerated recovery. Moreover, Kusumastiwi PO et al 15 undertaken a research to evaluate the treatment results of dressings containing a mixture of butyl aminobenzoate, eugenol, and iodoform, as well as other dry socket remedies, in terms of pain solace and socket curing, and they found that all of the treatments that include in the evaluation have the same goal of relieving the patient 's suffering. The findings are challenging to evaluate due to the variety of treatments and measuring scales used.…”
Section: Resultsmentioning
confidence: 99%